An analysis of Loan Loss Provisioning behavior and Cost Efficiency in Chinese Commercial Banks - Lyu, Guowen (2017)
Loan Loss Provisioning (LLPs) is a reserve that is based on the expected loan losses of commercial banks. It directly affects the stability of the banking industry. Therefore, strengthening the risk management of commercial banks and improving the reliability of information disclosure are crucial. We will use the Orbis Bank Focus system and World Bank to collect data from 2011 to 2015 in order to investigate LLPs behavior in Chinese commercial banks, and find out whether Chinese commercial banks utilise LLPs behavior to influence their earnings, manage their capital and conduct business cycle management in the sample data. In addition, the analysis of cost efficiency is indispensable. The results of this paper illustrate that no earnings and capital management behavior exist in Chinese commercial banks, but they have a pro-cyclical management behavior. This study also shows that the cost efficiency is insignificantly negative correlated with LLPs.